4 Steps To My Future (4STMF): protocol for a universal school-based pilot and feasibility study of a CBT-based psychoeducational intervention to support psychological well-being amongst young adolescents in the Western Cape, South Africa - Bronwynè J. Coetzee (Pilot and Feasibility Studies, 2022)
Abstract Background Mental health problems often emerge during middle childhood and adolescence. In South Africa, and in the context of high rates of poverty, violence, and adversity, many children are at a considerable risk for developing mental health problems. Access to and costs of mental health services preclude treatment for most. There is evidence that universal school-based prevention programmes are effective in well-resourced settings. However, little is known about the feasibility and acceptability of such programmes in low- and middle-income countries (LMICs), including South Africa. Methods This is a feasibility pilot study of 4 Steps To My Future (4STMF), a Cognitive Behaviour Therapy (CBT) school-based programme for young adolescents in the Western Cape, South Africa. This eight-session intervention will be delivered to children in grade 5 (aged 10–13 years approximately) attending two public government-run schools in the Western Cape, South Africa. We aim to enrol approximately 224 children in grade 5. We will randomise which school receives the intervention first and the other will be a delayed intervention group. We will train individuals with a post-graduate degree in psychology to facilitate the programme. We will collect demographic data on participants as well as data on primary (feasibility measures) and secondary outcomes (mental health and well-being measures). We will collect data at baseline, post-intervention, and at 1-month follow-up. Discussion This pilot study will provide data on the acceptability and feasibility of delivering a universal school-based prevention programme in South African schools. The study will provide preliminary data to inform the design of a full-scale randomised controlled trial (RCT) of a universal school-based mental health programme aimed at preventing mental health problems. Trial registration This trial is registered with the Pan African Clinical Trial Registry ( https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=10881 ) database, with unique identification number for the registry: PACTR202004803366609. Registered on 24 April 2020.